Assessing team effectiveness and affective learning in a datathon. (April 2018) - Piza, Felipe Maia de Toledo; Celi, Leo Anthony; Deliberato, Rodrigo Octavio; Bulgarelli, Lucas; de Carvalho, Fabricio Rodrigues Torres; Filho, Roberto Rabello; de La Hoz, Miguel Angel Armengol; Kesselheim, Jennifer Cohn
Highlights: Affective learning and team effectiveness skills were acquired by participants of a health datathon event in São Paulo, Brazil. Successful teams are associated with higher affective learning gains for participants. Effective leadership is essential for teamwork and is a significant predictor for learning. Abstract: Background: Datathons are increasingly organized in the healthcare field. The goal is to assemble people with different backgrounds to work together as a team and engage in clinically relevant research or develop algorithms using health-related datasets. Criteria to assess the return of investment on such events have traditionally included publications produced, patents for prediction, classification, image recognition and other types of software, and start-up companies around the application of machine learning in healthcare. Previous studies have not evaluated whether a datathon can promote affective learning and effective teamwork. Methods: Fifty participants of a health datathon event in São Paulo, Brazil at Hospital Israelita Albert Einstein (HIAE) were divided into 8 groups. A survey with 25 questions, using the Affective Learning Scale and Team-Review Questionnaire, was administered to assess team effectiveness and affective learning during the event. Multivariate regression models and Pearson's correlation tests were performed to evaluate the effect of affective learning on teamwork. Results: Majority of the participants were male 76% (37/49); 32% (16/49) were physicians. The mean score for learning (scale from 1 to 10) was 8.38, while that for relevance of the perceived teamwork was 1.20 (scale from 1 to 5; "1" means most relevant). Pearson's correlation between the learning score and perception of teamwork showed moderate association ( r  = 0.36, p  = 0.009). Five learning and 10 teamwork variables were on average positively graded in the event. The final regression model includes all learning and teamwork variables. Effective leadership was strongly correlated with affective learning (β = −0.27, p < 0.01, R 2  = 75%). Effective leadership, team accomplishment, criticism, individual development and creativity were the variables significantly associated with higher levels of affective learning. Conclusion: It is feasible to enhance affective knowledge and the skill to work in a team during a datathon. We found that teamwork is associated with higher affective learning from participants' perspectives. Effective leadership is essential for teamwork and is a significant predictor of learning.